Vasectomy: A Survey of Attitudes, Counseling Patterns and Acceptance among Nigerian Resident Gynaecologists - Ebeigbe, P N (Ghana Medical Association, 2011)
OBJECTIVES: Previous Nigerian studies show widespread ignorance and low acceptance of vasectomy among the male population. The objectives of this study were to determine the level of knowledge of, attitudes to, counselling pattern and acceptance of vasectomy among Nigerian Resident Gynaecologists. DESIGN: A cross-sectional questionnaire based survey. METHOD: Resident Doctors attending a national update course in obstetrics and gynaecology. RESULTS: Most of the doctors had good knowledge of Vasectomy. More than four-fifth of the doctors were convinced that the average Nigerian male will not accept vasectomy when indicated while more than threefifth consider BTL a more appropriate option for permanent contraception in our setting. Forty one point three percent of the doctors will opt for vasectomy or urge their husbands to. Reasons for opposition to vasectomy were socio-cultural (21.3%), religious (13.1%) and psychological (41.0%), 24.6% had no specific reasons. While 89.4% of the doctors counselled often for BTL only 5.8% did for vasectomy. CONCLUSION: The Doctors showed good knowledge of vasectomy but most were poorly disposed towards use of vasectomy. The findings suggest a need for effective national training programmes targeted at resident doctors to enhance their knowledge of vasectomy as well as break barriers to personal use of, and counselling for vasectomy.